SUPER ENCRYPTION OF TEXT DATA USING A HYBRID BEAUFORT VIGENERE CIPHER WITH BLUM BLUM SHUB PSEUDORANDOM KEYS - Fauzi, Achmad (STMIK KAPUTAMA, 2026)
Super encryption is a data security technique that combines multiple cryptographic methods to enhance message security. This study proposes a super encryption method using a combination of Vigenère Cipher and Beaufort Cipher algorithms, strengthened by the Blum Blum Shub pseudo-random key generator. The aim of this method is to secure text data by producing more complex and harder-to-crack encryption. The Vigenère Cipher is known for its polyalphabetic nature, while the Beaufort Cipher offers unique characteristics that distinguish it from other ciphers. The Blum Blum Shub pseudo-key generator ensures a high level of key randomness. The implementation of this method is expected to provide a practical and efficient solution for securing text data. The evaluation focuses on analyzing algorithm complexity, key randomness, and resilience against cryptographic attacks.